Determination of the influence of C24 D/(2R)- and L/(2S)-isomers of the CER[AP] on the lamellar structure of stratum corneum model systems using neutron diffraction. (December 2017) - Schmitt, Thomas; Lange, Stefan; Sonnenberger, Stefan; Dobner, Bodo; Demé, Bruno; Neubert, Reinhard H.H.; Gooris, Gert; Bouwstra, Joke A.
Graphical abstract: Highlights: Thed - andl -Isomer of the ceramide [AP] show notably different biophysical properties. Thel -Isomer of ceramide [AP] behaves unnatural and cannot be considered suitable for research or pharmaceutical applications. The content of ceramide [AP] was shown to be a major regulator of the inter-lamellar water content. A low biophysical redundancy of different ceramides, despite only small head group differences, could be emphasized. Abstract: This study was able to investigate the different influence of thed - andl -ceramide [AP] on the lamellar as well as molecular nanostructure of stratum corneum simulating lipid model mixtures. In this case, neutron diffraction together with specifically deuterated ceramide was used as an effective tool to investigate the lamellar and the molecular nanostructure of the mixtures. It could clearly be demonstrated, that both isomers show distinctly different characteristics, even though the variation between both is only a single differently arranged OH-group. Thel -ceramide [AP] promotes a crystalline like phase behaviour even if mixed with ceramide [NP], cholesterol and free fatty acids. Thed -ceramide [AP] only shows crystalline-like features if mixed only with cholesterol and free fatty acids but adopts a native-like behaviour if additionally mixed with ceramide [NP]. It furthermore demonstrates that thel -ceramide [AP] should not be used for any applications concerning ceramide substitution. It could however possibly serve its own purpose, if this crystalline like behaviour has some kind of positive influence on the SC or can be utilized for any practical applications. The results obtained in this study demonstrate that the diastereomers of ceramide [AP] are an attractive target for further research because their influence on the lamellar as well as the nanostructure is exceptionally strong. Additionally, the results furthermore show a very strong influence on hydration of the model membrane. With these properties, thed -ceramide [AP] could be effectively used to simulate native like behaviour even in very simple mixtures and could also have a strong impact on the native stratum corneum as well as high relevance for dermal ceramide substitution. The unnaturall -ceramide [AP] on the other hand should be investigated further, to assess its applicability.